The Role And Competence Of Sharia Auditors In Supporting The Performance Of Sharia Banking - Umi Suswati Risnaeni; Amalus Sholeha (Muhasabatuna : Jurnal Akuntansi Syariah, 2022)
This article aims to provide an overview of the role of shariah halal auditors in the guarantee system in sharia banking in Indonesia. Sharia banking is a financial institution that must be examined and tested with smart products, and it is operated by an independent institution which is a "sharia auditor" and must be considered by sharia auditors, namely sharia bank financial statements, SOP (System Operating Procedures), Sharia Human Resources (HR), Sharia supervisory board, and sharia product structure. Monitoring shari'ah banks and monitored by internal or external shari'ah auditors, while guarantees in Islamic law are divided into two namely: personal guarantees and property guarantees and are known as “kafalah or rahn”. The institution controls or monitors that internal or external shariah auditors must carry out internal shariah reviews conducted by shariah compliance officers, who control or monitor shariah compliance and "fatwa" decisions, instructions, guidelines, issued by the Shariah Oversight Board of the financial institution. .Sharia review, sharia internal review and sharia audit are important processes to ensure a halal assurance system for the operational activities of sharia financial institutions and their sharia products. Reports and recommendations from the Sharia Monitoring Board will be submitted to the National Sharia Monitoring Board for consideration.